2007
DOI: 10.1111/j.1365-2249.2007.03345.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of a new immunosuppressive agent, everolimus, on interleukin-10 gene-deficient mice with colitis

Abstract: SummaryA limited number of therapeutic strategies are currently available for patients with inflammatory bowel disease (IBD). In particular, the maintenance therapy after remission in Crohn's disease (CD) is not satisfactory and new approaches are needed. Interleukin-10 gene-deficient (IL-10 -/-) mice, a wellcharacterized experimental model of CD, develop severe chronic colitis due to an aberrant Th1 immune response. Everolimus, an inhibitor of the mammalian target of rapamycin (mTOR), a new immunosuppressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…A growing body of evidence supports the notion that kinase inhibitors, which possess antiproliferative activities, are potential therapeutics for UC (15,34,39). In our search for anticancer therapeutics, we have found that P2281 inhibits mTOR activity in colon cancer cells and suppresses DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…A growing body of evidence supports the notion that kinase inhibitors, which possess antiproliferative activities, are potential therapeutics for UC (15,34,39). In our search for anticancer therapeutics, we have found that P2281 inhibits mTOR activity in colon cancer cells and suppresses DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, a recent study showed that rapamycin, a mTOR inhibitor, blunts leukocyte adhesion and extravasation in the gut mucosa, leading to suppression of experimental chronic colitis (15). In a complementary study, treatment with everolimus (another mTOR inhibitor) reduced the number of T cells in lamina propria and blocked lymphocytic IFN-␥ release, thereby ameliorating established murine colitis (34). These findings suggest that mTOR inhibitors may be useful for treatment of UC.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…115 A similar drug to sirolimus, everolimus, is also an inhibitor of MTOR and has previously been demonstrated to produce promising results in murine colitis. 116 However, everolimus treatment failed to produce a significant difference in a randomized, controlled clinical trial for Crohn disease that was prematurely terminated after only 96 patients were evaluated (36 of whom received everolimus), likely due to the influence of disease-related factors on pharmacokinetics and pharmacodynamics or on the dosage regimens applied. 117 Nevertheless, the successful use of sirolimus in a so far underpowered clinical setting suggests that the efficacy of MTOR-based pharmaceutical strategies should be evaluated in randomized clinical trials among patients with Crohn disease refractory to conventional treatment, i.e., immunomodulators and biologics.…”
Section: Atg16l1-dependent Signaling In Crohn Diseasementioning
confidence: 99%